Chronic low back pain management in rural Cameroon: a pragmatic pilot study of osteopathic care, physiotherapy, and the “unique practitioner syndrome” - Moumeni, Ibrahim Npochinto; Moumeni, Abdel-Nasser Njikam; Orlsiter, Tchuidjio Ketchogue Bristher; Atemkeng-Tsatedem, Fausting (Frontiers in Musculoskeletal Disorders, 2026)
BackgroundChronic low back pain (CLBP) affects 14%–72% of African populations, yet evidence comparing manual therapy approaches in sub-Saharan Africa remains scarce. In rural settings characterized by limited therapeutic options, care often becomes informally centralized around practitioners with rare expertise. This pilot study compared osteopathic care and physiotherapy for CLBP in rural Cameroon, while exploring contextual mechanisms underlying healthcare-seeking behaviors, including the “unique practitioner syndrome.”MethodsThis pragmatic pilot exploratory study was conducted at Bafoussam Regional Hospital between January 2023 and December 2024, with the primary objective of generating preliminary comparative signals and informing future randomized controlled trials. Patients were allocated according to consultation day: osteopathic care (Monday/Wednesday, n = 19) and physiotherapy (Tuesday/Thursday/Friday, n = 28), reflecting real-world service organization. Primary outcomes included pain intensity (Visual Analog Scale, VAS) and functional disability (Eifel Disability Index). Secondary outcomes comprised a newly developed Therapeutic Autonomization Score and a culturally adapted Agricultural Functional Test. Quantitative outcomes were complemented by qualitative patient narratives to explore experiential and psychosocial dimensions of care.ResultsForty-seven patients completed the intervention (78.7% women; mean age 44.8 ± 12.3 years), with 95.7% reporting prior unsuccessful physiotherapy. Across the 5-week intervention period, larger magnitudes of improvement were observed in the osteopathic care pathway compared with physiotherapy for pain reduction (−47.3% vs. −32.1%; p = 0.008; Cohen's d = 0.85) and functional disability (−42.8% vs. −31.5%; p = 0.018; Cohen's d = 0.73). Higher autonomization scores were also observed in the osteopathy group (16.2 ± 2.3 vs. 13.8 ± 3.1; p = 0.005). Osteopathic care required fewer treatment sessions (9.8 ± 0.9 vs. 14.1 ± 1.2; p < 0.001), with associated reductions in direct treatment costs. Qualitative narratives highlighted distinct experiential patterns, supporting contextual mechanisms such as credential-based therapeutic authority and therapeutic scarcity dynamics.ConclusionsThis pragmatic pilot study identified preliminary between-group differences favoring the osteopathic care pathway in a highly selected population with prior treatment failure. However, non-randomized allocation, unequal treatment dose, investigator involvement in care delivery and assessment, and strong contextual influences substantially limit causal inference and generalizability. These findings should be interpreted as exploratory comparative signals rather than evidence of treatment superiority. Confirmation through rigorously designed, adequately powered randomized controlled trials with blinded assessment and extended follow-up is required. Nonetheless, the study provides valuable methodological, contextual, and conceptual insights to guide future rehabilitation research and service organization in resource-limited African settings.